M. A. Mehmed, Istorija Turcilor, Bucuresti 1976 - Vanku, Milan (Balcanica - Annual of the Institute for Balkan Studies, 2023)
Mustafa Ali Mehmed, Istoria Turcilor [History of the Turks], București, 1976, pp. 447.